Indolium 1 Exerts Activity against Vemurafenib-Resistant Melanoma In Vivo - Rakan Radi; Christina Huang; Justin Elsey; Yoon H. Jung; Victor G. Corces; Jack L. Arbiser (MDPI AG, 2022)
The development of targeted therapies (BRAF/MEK inhibitors) and immunotherapy have had a major impact on the treatment of melanoma. However, the majority of patients with advanced melanomas succumb to their disease. The mechanisms of resistance to both targeted therapies and immunotherapies are numerous and have been well-described. These include the alternative activation of BRAF/MEK signaling, novel compensating mutations in additional oncogenes, and loss of neoantigens. There has been limited development of small molecules that target alternative pathways in melanoma in the last two decades. We have previously identified triphenylmethanes as a class that shows activity against a wide variety of tumors. We have synthesized a novel triphenylmethane, indolium 1, and demonstrated its efficacy against an aggressive vemurafenib-resistant melanoma in vivo. Indolium 1 has a novel mechanism of action against melanoma, in that it results in induction of the tumor-suppressor EPHA3. We believe that pre-IND studies are warranted for this novel compound, given its mechanism of action and ability to inhibit the growth of vemurafenib resistant melanoma in vivo.